2015
DOI: 10.15628/holos.2015.2160
|View full text |Cite
|
Sign up to set email alerts
|

EFEITO DO MÉTODO DE COMPLEXAÇÃO COMBINANDO EDTA - CITRATO E COPRECIPITAÇÃO EM MEIO OXALATO NA SÍNTESE DA SrCo0,8Fe0,2O3-d

Abstract: La 2 Ce 2 O 7 foi obtido utilizando a metodologia de coprecipitação via oxalato. A relação ácido oxálico, oxalato de amônio e nitrato de lantânio e cério usada foi de 1:1:1:1, o pH 10 foi mantido durante a síntese através da adição de trietilamina. Para a caracterização, a amostra foi submetida às análises de DRX, MEV com mapeamento EDS e cálculo do tamanho do cristalito pela equação de Scherrer. As análises realizadas mostraram que o cerato de lantânio foi formado em sua forma pura, cúbica, sem interferência … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
3
0
4
Order By: Relevance
“…The EDTA-Citrate complexation method based on the methodology described by SANTOS et al [10], SILVA et al [11] and SILVA et al [17] is shown in Figure 1 and briefly described below: initially, some amount of acidic EDTA was diluted in ammonium hydroxide at a ratio of 1 g:10 mL and kept under controlled stirring and heating (solution 1), then to solution 2 (Fe(NO 3 ) 3 .9H 2 O) and then solution 3 (Cu(NO 3 ) 2 .3H 2 O) was added to solution 1 and then solution 4. Subsequently citric acid was added (solution 4) and then the temperature was increased and controlled by about 80 °C until gel formation.…”
Section: Synthesis Of Copper Ferrite By Edta-citrate Complexation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDTA-Citrate complexation method based on the methodology described by SANTOS et al [10], SILVA et al [11] and SILVA et al [17] is shown in Figure 1 and briefly described below: initially, some amount of acidic EDTA was diluted in ammonium hydroxide at a ratio of 1 g:10 mL and kept under controlled stirring and heating (solution 1), then to solution 2 (Fe(NO 3 ) 3 .9H 2 O) and then solution 3 (Cu(NO 3 ) 2 .3H 2 O) was added to solution 1 and then solution 4. Subsequently citric acid was added (solution 4) and then the temperature was increased and controlled by about 80 °C until gel formation.…”
Section: Synthesis Of Copper Ferrite By Edta-citrate Complexation Methodsmentioning
confidence: 99%
“…There are different techniques from which these materials can be synthesized, including sol-gel [2], co-precipitation [7], solvothermal [8], combustion [1], hydrothermal synthesis and EDTA-Citrate complexation [9]. This latter method has been widely used for the production of ceramic powders due to its numerous advantages, such as easy control of stoichiometry, high purity and crystallinity of the products, since the choice of a chemical process is very important to obtain good quality ferrite [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The perovskite of composition BaCe 0.8 Pr 0.05 Cu 0.15 O 3-δ was synthesized by the EDTA-citrate method 9,22,23 using the chemicals listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…: a perovskita BaCeO 3 foi sintetizada com base no método de complexação combinando EDTA-citrato [14,15]. O método consiste na diluição do EDTA ácido em hidróxido de amônia (1 g: 10 mL), sob agitação e aquecimento (40 °C), com posterior introdução dos respectivos metais; e adição do ácido cítrico seguido do aumento da temperatura até 80 °C.…”
Section: Síntese Do Catalisador (Baceo 3 )unclassified